2021
DOI: 10.1017/s0373463321000485
|View full text |Cite
|
Sign up to set email alerts
|

Consistency analysis of global positioning system position errors with typical statistical distributions

Abstract: Research into statistical distributions of φ, λ and two-dimensional (2D) position errors of the global positioning system (GPS) enables the evaluation of its accuracy. Based on this, the navigation applications in which the positioning system can be used are determined. However, studies of GPS accuracy indicate that the empirical φ and λ errors deviate from the typical normal distribution, significantly affecting the statistical distribution of 2D position errors. Therefore, determining the actual statistical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…The actual physical system is generally continuous, and the dynamic characteristics are described by continuous differential equations. Therefore, the discretizations of the system equation and the observation equation are needed [ 28 , 29 ].…”
Section: The Application Of Kalman Filter In the Error Modelmentioning
confidence: 99%
“…The actual physical system is generally continuous, and the dynamic characteristics are described by continuous differential equations. Therefore, the discretizations of the system equation and the observation equation are needed [ 28 , 29 ].…”
Section: The Application Of Kalman Filter In the Error Modelmentioning
confidence: 99%
“…Referring to selected works, it is sufficient to cite that in 2014, it was 3.351 m [5], while in 2017, it was 1.891 m [6]. An extensive study conducted in 2021 [7] shows that the current GPS positioning accuracy is 2.393 m (p = 0.95). In a subsequent paper, the same author [8] experimentally determined, based on 900,000 fixes, the numerical relationships between the 2D position error and the different HDOP values.…”
Section: Introductionmentioning
confidence: 99%
“…It must be noted that the quality of a photogrammetric study is affected by many factors, the specific division of which can be found in paper [23]. The most important factors include: object shape and colour [24,25], image quality [26], used software, methods [22,27], used sensors [28], accuracy of support systems [29][30][31][32] and data fusion methods [33][34][35], sensor orientation [1] or even the sensor's temperature [36]. In this study, we focus only on the illumination of 3D urban mock-up lighting scene(s).…”
Section: Introductionmentioning
confidence: 99%